Coagulation pathways and diabetic retinopathy: abnormal modulation in a selected group of insulin dependent diabetic patients. Issue 6 (1st June 2000) - Giusti, Cristiano; Schiaffini, Riccardo; Brufani, Claudia; Pantaleo, Antonio; Vingolo, Enzo Maria; Gargiulo, Patrizia
Abstract : AIMS: To investigate whether diabetic retinopathy (DR), already associated with microvascular alterations, ischaemia, and endothelial dysfunction, was also characterised by abnormal modulation of coagulation pathways. METHODS: Plasma samples, collected from 67 type 1 diabetics comparable for age, duration of disease (DD), and metabolic control (MC), were processed for prothrombin degradation products (F1+2) and factor VII coagulant activity (FVII:c). 50 normal subjects served as a control group. The ETDRS-Airlie House Classification of DR was used. RESULTS: A significant correlation between FVII:c and F1+2 plasma concentrations was observed (p <0.05). FVII:c (p <0.005) and F1+2 (p <0.0001) levels were higher in diabetics than in controls, especially in patients with proliferative DR (FVII:c p <0.0001; F1+2 p<0.005). However, cases without retinal lesions and healthy subjects did not differ significantly (FVII:c and F1+2 p >0.05). CONCLUSIONS: These findings pointed out the presence of a hypercoagulable state associated with endothelial dysfunction in patients with insulin dependent diabetes mellitus (IDDM), demonstrated both by increased FVII:c and F1+2 plasma levels. Moreover, the observation of different DR related degrees of procoagulant activity, despite comparable DD and MC, strengthens the hypothesis of multiple risk factors in the pathogenesis of DR.